2011
DOI: 10.5301/jva.5000024
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Oxidation and Venous Neointimal Hyperplasia Precede Vascular Injury from AVF Creation in CKD Patients

Abstract: Purpose Intimal hyperplasia (IH), a well-recognized cause of dialysis vascular access failure, is generally believed to be an acquired pathologic lesion. Recent data suggests that IH is present prior to AVF creation. We sought to determine whether pre-existing inflammation and oxidation co-exist with IH prior to their incorporation into an AVF conduit, as their presence may predispose the AVF to further IH following AVF creation. Methods At the time of first AV access surgery, vein segments were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 15 publications
(17 reference statements)
2
84
1
Order By: Relevance
“…One potential explanation is that, in patients with comorbidities that may lead to endothelial dysfunction and vascular wall abnormalities, the hemodynamic shear stress of an AVF might cause increased neointimal hyperplasia with a lack of vascular dilation. 29 Because a significant degree of neointimal hyperplasia has been found at the site of the vascular access placement in patients with CKD before AVF creation, 30,31 placing an AVF too early in patients with CHF or diabetes may increase the exposure time to neointimal hyperplasia and thereby, AVF failure.…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation is that, in patients with comorbidities that may lead to endothelial dysfunction and vascular wall abnormalities, the hemodynamic shear stress of an AVF might cause increased neointimal hyperplasia with a lack of vascular dilation. 29 Because a significant degree of neointimal hyperplasia has been found at the site of the vascular access placement in patients with CKD before AVF creation, 30,31 placing an AVF too early in patients with CHF or diabetes may increase the exposure time to neointimal hyperplasia and thereby, AVF failure.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, preexisting intimal hyperplasia has been observed in the native veins used to create an AVF in CKD patients (10,11). It is possible that preexisting venous intimal hyperplasia predisposes those patients to more aggressive venous neointimal hyperplasia after AVF creation, thereby contributing to AVF stenosis and presumably, AVF nonmaturation and inferior long-term AVF outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it also results in significant endothelial and medial smooth muscle cell damage, and the vessel wall invariably responds with an increased cellular proliferation within the neointima and, subsequently, a more aggressive neointimal hyperplasia development (13). Although most of the data on angioplasty-induced neointimal hyperplasia come from studying arterial models (14,15), it is also very likely that there is a deleterious injury from angioplasty to the venous system, especially because the venous tissue has intrinsically high baseline levels of inflammation and oxidative stress (16,17) from the uremic milieu.…”
Section: Histopathology Following Endovascular Repairmentioning
confidence: 99%
“…Recently, several studies have demonstrated that neointimal hyperplasia is present in the majority of patient veins at the time of surgical creation (16)(17)(18) (Figure 1B), suggesting that the health of the vein at the time of AVF creation may also play an important role in AVF nonmaturation. Moreover, initial results from the multicenter National Institutes of Health Fistula Maturation Study have reported that 87.8% of vein samples examined to date (n5204; total planned enrollment, 600 participants) have neointimal hyperplasia (19).…”
Section: Histopathology Of Uremic Vessels Prior To Vascular Access Crmentioning
confidence: 99%